Atomic Habits Parenting Validating a Behavioral Framework for Stunting Prevention - Sirajuddin Sirajuddin; Mustamin Mustamin; Dien Abdul Munir (Journal of Public Health and Pharmacy)
Introduction: Atomic Habits Parenting focuses on small, consistent actions by caregivers to detect and prevent stunting in children. A valid and reliable instrument is essential for early detection and effective prevention. This study aims to evaluate the validity and reliability of the Atomic Habits Parenting instrument and its association with stunting prevention in children under five. This method differs from others as the consistent daily practice of small habits leads to a 37-fold improvement over one year.